Konsep diri pada mahasiswa yang memiliki jerawat tingkat sedang dan berat di fakultas ilmu kesehatan universitas muhammadiyah purwokerto - Mega Agustin Cahyandari; Suci Ratna Estria (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: To find out the self concept in students who have acne and weight level sedan in the Faculty of Health Sciences, University of Muhammadiyah Purwokerto.Methods: This study used descriptive qualitative method with phenomenological approach. The samples in this research were 9 participants who are students semester 1, 3, 5, and 7. The sampling method using purposive sampling.Results: Research results obtained include a self-concept that consists of body image, self-identity, the role of self, ideal self, and self-esteem. 7 of 9 participants felt ashamed, withdraw / covering his face with a mask thereby affecting her confidence. All the participants can assess themselves and be confident to mention the benefits and drawbacks, still play an active role both in the campus environment, family and community circles. Have a realistic desire and attitude standards-compliant private individuals. 7 of 9 participants had low self esteem because facial acne while 2 of 9 participants have high self esteem.Conclusion: From the results of the study, it was found that not all students self-concepts were impaired. Of the five self-concepts found that adolescents experience disturbances in body image and self-esteem.